Connecting Food Staples and Input Markets in West Africa : A Regional Trade Agenda for ECOWAS Countries - Maur, Jean-Christophe; Shepherd, Ben (World Bank, Washington, DC, 2015)
The report Africa Can Help Feed Africa (World Bank 2012) showed that increasing food staples1 supply can be met by better connecting African markets to each other. That report called for a stronger focus on removing trade barriers and building on the forces of regional integration. This report builds on the lessons of Africa Can Help Feed Africa by looking into the specific circum¬stances met in West Africa, home to one-third of the continent’s population and to some of its most vulnerable countries. Staple foods are the main source of calories in Africa and in West Africa. In that region, rice, followed by maize and cassava, provides the main source of calories in coastal countries, with millet and sorghum being an important source of food in Sahelian countries (Haggblade et al. 2012). The challenge of food supply is particularly acute in West Africa with some of the world’s fastest growing populations, including urban populations. West Africa’s 2011 population of 342 million is expected to increase to 516 million by 2030 and to 815 million by 2050 (United Nations Department of Economic and Social Affairs, Population Division 2013); in this time frame, the region’s urban population will grow from 44 percent to 63 percent of the total population (United Nations Department of Economic and Social Affairs, Population Division 2014). As this report will show, strong reasons exist to bring a more strategic focus on promoting regional trade. The first compelling reason is that there is already a sizeable amount of trade in the region, revealing existing important complementarities between countries in the ECOWAS space. Because a large share of this trade is informal, this reality is not always well taken into account. A second reason is that developing these complementarities by facilitating trade and creating the regional soft and hard infra¬structure to incite cross-border flows would further enable (a) the exploitation of comparative advan¬tages and economies of scale in the region; (b) access to and diffusion of better production technologies; (c) competitive access to inputs, research, and extension services; and (d) improved security in the face of shocks that lead to food crises. Finally, a third reason is that existing national policies that affect trade are, by and large, inefficient and incoherent at the regional level; therefore a better use of policy making and institutions is needed to achieve food policy objectives.